Pengaruh Reputasi Merek, Kualitas Produk dan Keunikan Produk Terhadap Kepuasan Pelanggan Pakaian Thrift Shop Di Kota Bandung - sahputra, Rizky Darwisy; Gumilar, Dedi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine how consumer satisfaction is influenced by brand reputation, product quality, and product uniqueness, using a quantitative approach that combines descriptive and verification methods. Data were collected through questionnaires and a literature review, with a total sample of 100 respondents selected using the Slovin formula. The analysis employed SPSS version 25 to test the hypotheses and determine the relationships among variables. The results show that brand reputation has no significant effect on consumer satisfaction, indicated by an alpha value of 0.143 and a significance level of 0.152. In contrast, product uniqueness demonstrated a significant positive effect, with a t-value of 3.621 and a significance level of 0.000. Similarly, product quality was found to have a strong and significant impact on consumer satisfaction, reflected by a t-value of 6.987 and a significance level of 0.000. When analyzed simultaneously, the three variables brand reputation, product quality, and product uniqueness collectively exert a significant influence on customer satisfaction, as evidenced by an F-value of 281.066 and a significance level of 0.000. These findings suggest that while brand reputation alone may not directly enhance satisfaction, superior product quality and uniqueness play a crucial role in shaping positive consumer perceptions and overall satisfaction levels.